THE EFFECT OF SOCIAL MEDIA MARKETING AND ONLINE CUSTOMER REVIEW ON PURCHASE DECISIONS IN STUDENTS - Nasaruddin, Nasaruddin Nasaruddin; Wonua, Almansyah Rundu; Ismanto, Ismanto Ismanto (Program Studi Manajemen Fakultas Ekonomi Universitas Siliwangi, 2023)
This study aims to determine the effect of Social Media Marketing and Online Customer Review on the purchase decision of Scarlett Whitening among students at the University of Nineteen November Kolaka. This research uses a quantitative approach. Collecting data in this study using observation, documentation, and questionnaires. The population of this study were students of Sembilanbelas november Kolaka University. While the sample of this study amounted to 150 people according to the results of the hair formula. Testing research instruments using validity and reliability tests with SPSS 25.0. The data analysis technique used in this study is the measurement model test (outer model) and the structural model test (inner model) with Smart PLS 4.0. Based on the results of the research, it is known that there is a positive and significant influence between the Social Media Marketing variable on the purchase decision of Scarlett Whitening in Kolaka Nineteen November University Students. Meanwhile, the Online Customer Review variable on the purchase decision of Scarlett Whitening for students at the Sembilanbelas november Kolaka University has a positive and significant effect.